2020
DOI: 10.17109/azh.66.suppl.147.2020
|View full text |Cite
|
Sign up to set email alerts
|

High molecular diversity in Carabus (Hygrocarabus) variolosus and C. nodulosus

Abstract: The Carabus subgenus Hygrocarabus contains two taxa: C. variolosus and C. nodulosus, the species or subspecies status of which is handled far from uniform in the literature. Both taxa show a similar morphology, the shape of the tip of the aedeagus provides a reliable morphological marker for identification. We analysed two mitochondrial gene parts (COI-5’ and COI-3’) and a nuclear one (ITS2). High diversity was found showing specific geographical patterns. Introgressive hybridisation was detected but interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
3
3
Order By: Relevance
“…Within Carabus ( Hygrocarabus ), we recover C. variolosus nested within C. nodulosus . This result contrasts with the ones of Mossakowski et al . (2020) where the two species were suggested to be well differentiated genetically.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Within Carabus ( Hygrocarabus ), we recover C. variolosus nested within C. nodulosus . This result contrasts with the ones of Mossakowski et al . (2020) where the two species were suggested to be well differentiated genetically.…”
Section: Discussioncontrasting
confidence: 99%
“…Except for a minority of analyses, our results strongly suggest that C. ( Hygrocarabus Within C. (Hygrocarabus), we recover C. variolosus nested within C. nodulosus. This result contrasts with the ones of Mossakowski et al (2020) where the two species were suggested to be well differentiated genetically. In their study, these authors argued based on the analysis of two gene fragments that both taxa form distinct clades although several specimens caused each species to be paraphyletic.…”
Section: Systematics and Species Delimitation In Arciferacontrasting
confidence: 89%
See 3 more Smart Citations